Amino acid systems in the interpeduncular nucleus are altered in a sex‐dependent manner during nicotine withdrawal. Issue 8 (22nd March 2021) - Carcoba, Luis M.; Uribe, Kevin P.; Ortegon, Sebastian; Mendez, Ian A.; DeBiasi, Mariella; O'Dell, Laura E.
Abstract: Prior work in male rodents established that the medial habenula‐interpeduncular nucleus (MHb‐IPN) pathway modulates nicotine withdrawal. Specifically, withdrawal severity has been closely associated with inhibitory tone in the IPN via interneurons that release γ‐aminobutyric acid (GABA). Inhibitory tone in the IPN is regulated by projections from the MHb that co‐release glutamate and acetylcholine. Within the IPN, inhibitory tone is also regulated via corticotropin‐releasing factor type 1 (CRF1) receptors that control GABA release from local interneurons. This study extends previous work by comparing sex differences in GABA, glutamate, as well serotonin levels in the IPN during precipitated nicotine withdrawal. Sex differences in withdrawal‐induced neurochemical effects were also compared following systemic administration of a CRF1 receptor antagonist. The results revealed that there were no group differences in serotonin levels in the IPN. A major finding was that females displayed a larger withdrawal‐induced increases in GABA levels in the IPN than males. Also, withdrawal increased IPN glutamate levels in a similar manner in females and males. Blockade of CRF1 receptors produced a larger suppression of the withdrawal‐induced increases in GABA levels in the IPN of females versus males, an effect that was likely related to the robust increase in glutamate following administration of the CRF1 receptor antagonist in females. These data suggest that amino acid systems in the IPN modulate sex differences in the behavioral effects of nicotine withdrawal. Furthermore, our data imply that medications that target stress‐induced activation of the IPN may reduce withdrawal severity, particularly in females. Abstract : Females displayed a greater withdrawal‐induced increase in interpeduncular nucleus (IPN) γ‐aminobutyric acid levels than males. This measure of inhibitory tone was suppressed to a larger extent in females following blockade of corticotropin‐releasing factor type 1 (CRF1) receptors, an effect that was likely due to greater CRF innervation of the IPN in females following chronic nicotine exposure.